Driven to survive four Filipino women CEOs' stories on separation or annulment - Go, Chiqui Escareal (Philippine Social Sciences Review, 2014)
Discussions of the divorce issue in the Philippines have largely focused on women’s concerns, given that marriage and relationships are gendered experiences shaped by traditional roles and expectations where women are seen at a disadvantage. Women’s groups have emphasized the need for divorce for poor women who are victims of violence or whose sense of self is lost amidst domestic abuse. This paper examines the stories of separation or annulment of four women CEOs who are highly educated and economically empowered, to explore how they handled domestic and marital challenges, and to create awareness on the issue of divorce that is truly inclusive for all women of whatever socio-economic class. Using a qualitative approach, purposive sampling is used and four women CEOS were interviewed indepth to analyze factors beyond demographics, that included personal values and beliefs on religion, society, family, and gender roles. The study yields that economically empowered Filipino women go through almost the same marital conflicts as women from other socio-economic classes and as such their views on or acceptance of divorce or annulment may take the same direction in claiming back a sense of self or protection from any form of violence. These are issues that might have been overlooked in the divorce discussion precisely because these women’s education and social levels as well as their economic or financial independence are assumed to protect or shield them from possible abuse (physical, mental, emotional, and verbal) in the domestic domain.